The Evaluation of the Effect of Hypothyroidism Treatment on Non-Alcoholic Fatty Liver Disease - Ebadi, Seyed Alireza; Khalili, Shayesteh; Rafiei, Romina; Pishgahi, Mehdi; Shahrzad, Mohammad karim (Archives of Men's Health, 2021)
Introduction: There is still controversy over the existence of a relation between hypothyroidism and fatty liver disease. The scale by which hypothyroidism can affect fatty liver disease progression is also to be determined. Therefore, our study aims to contribute in the determination of this relation. Materials and methods: This observational analytical-before and after study with 53 patients was conducted. The subjects were categorized as having either primary or subclinical hypothyroidism. The serum levels of thyroid stimulation hormone (TSH), free T3 (FT3), free T4 (FT4), alanine transaminase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (ALP) were measured and liver ultrasound was done to screen nonalcoholic fatty liver disease (NAFLD). Results: The study consisted of 41 women and 12 men with the mean age of 48.3 years. The mean TSH levels decreased after hypothyroidism treatment in patients. The mean levels of FT4 did not have a significant increase after treatment, although in patients with subclinical hypothyroidism this increase was significant. T3 levels increased significantly after treatment. Statistical studies showed that there was a significant change in the degree of fatty liver before and after hypothyroidism treatment. Conclusion: There was an explicit relation between hypothyroidism and non-alcoholic fatty liver disease as Hypothyroidism treatment can prevent non-alcoholic fatty liver disease progression.